Nonpharmacologic and Nonsurgical Weight Management Interventions for Patients With Advanced CKD: A Scoping Review of the Medical Literature - Kamel Omer; Kristin K. Clemens; Yunxu Zhu; Heather LaPier; Louise Moist; Jaclyn Ernst; Sonja M. Reichert; Alla Iansavichene; Michael Chiu (Kidney Medicine)
Rationale & Objective: Obesity is associated with morbidity and mortality in people with chronic kidney disease (CKD). Identifying safe and effective nonpharmacologic and nonsurgical interventions to achieve a healthier body weight is essential. Study Design: Scoping review of observational studies and randomized control trials. Setting & Study Populations: Adults aged ≥18 years with a body mass index (BMI) ≥30 kg/m2 and advanced CKD (category G3-G5D). Selection Criteria for Studies: Following the Preferred Reporting Items for Systematic Reviews and Meta-analyses Extension for Scoping Reviews (PRISMA-ScR), we systematically searched 2 electronic databases (MEDLINE and Embase) for studies that examined the effect of nonpharmacologic and nonsurgical interventions for weight loss between January 2010-July 2024. Outcomes included weight loss and BMI. We also examined adherence, whether participants were involved in the design of the study, and adverse events. Data Extraction: Two reviewers screened relevant citations and extracted study characteristics and outcomes. Discrepancies were resolved by a third reviewer. Analytical Approach: Study data were summarized descriptively following guidance from the PRISMA-ScR. Results: Of the 2,453 citations, 17 met inclusion criteria (9 randomized controlled trials, 2 nonrandomized trials, 5 prospective cohort studies, and 1 retrospective cohort study) and included a total of 960 participants. Interventions included exercise programs, dietary therapy, and/or cognitive behavioral therapy with follow-up ranging from 3-12 months. It appeared that dietary intervention that promoted significant caloric restriction over the short term led to the most weight loss (average, 7 kg). Interventions with monitored coaching appeared helpful. No adverse events were reported. None of the studies involved participants as partners. Limitations: Not all studies included participants’ estimated glomerular filtration rate or BMI category, and we may have included some without severe CKD or BMI ≥30 kg/m2. Conclusions: Programs encouraging very low-energy diets along with monitored coaching, may result in modest short-term weight loss. Patient views on these programs and their longer term success remain unclear.